Assistance in identifying the potential of the Kembang Kuning tourist village, Cepogo District, Boyolali - Rina Sari Kusuma; Ratri Kusumaningtyas; Nieldya Nofandrilla; Budi Santoso; Vinisa Nurul Aisyah; Yanti Haryanti; Yudha Wirawanda (Universitas Muhammadiyah Magelang, 2023)
Tourism is one of the pillars of the local economy in Indonesian society, and as such, this sector should receive special attention to maintain and develop it. The COVID-19 pandemic has caused significant economic disruption, leading to a prolonged crisis. Kembang Kuning Village in Boyolali is an example of a tourism industry that possesses natural and cultural resources, which could serve as capital to establish a tourist village but has been hindered by the pandemic. This mentoring activity aims to revitalize tourist villages by identifying their potential. The service method includes traning and education of SWOT analysis. The results of the service demonstrate that there are strategies that Kembang Kuning Village can implement to not only restore local residents' income from the tourism sector but also enhance the quality of the existing tourist villages.